2013
DOI: 10.1002/anie.201300292
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless Dehydrogenation of Nitrogen Heterocycles with a Versatile Iridium Catalyst

Abstract: Gas up: A cyclometalated iridium complex is found to catalyze the dehydrogenation of various benzofused N‐heterocycles, thus releasing H2. Driven by as low as 0.1 mol % catalyst, the reaction affords quinolines, indoles, quinoxalines, isoquinolines, and β‐carbolines in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
110
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(117 citation statements)
references
References 33 publications
6
110
0
1
Order By: Relevance
“…We have previously shown that cyclometallated iridium complexes catalyse the hydrogenation of imino bonds and isolated their hydride complexes 26. The ability of such complexes to effect dehydrogenation of amines was also demonstrated,23b providing evidence that the cross‐coupling of amines may proceed via a similar pathway. The beneficial effect of TFE as solvent might stem from its strong hydrogen‐bond‐donating ability, which could promote the dissociation of the chloride anion from 1 e to form the active catalyst and/or activate the imine toward hydride transfer (Scheme ).…”
Section: Methodsmentioning
confidence: 92%
“…We have previously shown that cyclometallated iridium complexes catalyse the hydrogenation of imino bonds and isolated their hydride complexes 26. The ability of such complexes to effect dehydrogenation of amines was also demonstrated,23b providing evidence that the cross‐coupling of amines may proceed via a similar pathway. The beneficial effect of TFE as solvent might stem from its strong hydrogen‐bond‐donating ability, which could promote the dissociation of the chloride anion from 1 e to form the active catalyst and/or activate the imine toward hydride transfer (Scheme ).…”
Section: Methodsmentioning
confidence: 92%
“…Reversible hydrogen generation and storage on a potent chemical compound is an alternate solution to the staggering fuel crisis and is being actively pursued these days [298]. Towards this ultimate objective, the Ni−NHC complexes have been reported to successfully generate hydrogen by electro catalytic method (Scheme 46).…”
Section: Dehydrogenation Reactionmentioning
confidence: 98%
“…Our initial efforts to employ Pd-based catalysts led to unsatisfactory results, and we turned our attention to bioinspired ortho -quinone-based catalysts that are effective for the aerobic dehydrogenative aromatization of (partially) saturated nitrogen heterocycles. 7-9 Collectively, the aerobic dehydrogenation methods represent compelling alternatives to established methods that use stoichiometric reagents, such as DDQ or sulfur. 10 In light of the challenges we encountered in the use of Pd-based catalysts for N -heterocycle dehydrogenation, specifically to access quinoline products (Scheme 1A), we elected to test heterogeneous Co-oxide-based catalysts for this application.…”
mentioning
confidence: 99%